Biotechnological potential of Pedobacter lusitanus NL19 a new specie isolated from sludge from an uranium mine in Portugal - Covas, Cláudia de Jesus Fernandes (2024)
Bioactive natural products (BNPs) play an important role in our daily lives, especially as therapeutic agents. One example is antibiotics, which have been widely used in human health. The inappropriate use of these antibiotics has led to an increase in bacterial resistance, which is a problem of worldwide concern, warning for the urgent need for new effective alternatives. Extreme environments have already proven to be a rich source of microorganisms producing new chemical entities with important biological properties, namely antimicrobials. In the present study one such environment was explored. We have isolated several bacteria from sludges contaminated with radionuclides and metals, collected from a uranium mine run-off in Quinta do Bispo, Viseu, Portugal. One strain was selected based on its broad activity against Grampositive and Gram-negative bacteria, and also yeasts, with relevance in the clinical, food, veterinary and aquaculture settings. The phylogenetic analysis of the 16S rRNA, gyrB and Internal Transcribed Spacer (ITS) gene sequences identified this strain as belonging to the genus Pedobacter, and having P. himalayensis, P. cryoconitis, P. westerhofensis and P. hartonius as closely related species. Further polyphasic analysis showed that the strain is a new bacterial species, and which was named Pedobacter lusitanus NL19. In silico analysis of NL19 genome sequence revealed the presence of 17 biosynthetic gene clusters (BGCs) for different classes of BNPs, including nonribosomal peptide (NRPs), polyketides (PKs), ribosomally synthesized and posttranslationally modified peptides (RiPPs), siderophores, terpenes and several hybrid NRPs-PKs. NL19 bioactivity was detected in solid medium but not in its equivalent broth. Further investigations showed that a high concentration of peptone from casein (PC) was the main factor associated with the lack of bioactivity by NL19 in broth. On the contrary, in broth with a low concentration of PC, the compounds produced by NL19 showed a broad spectrum of activity against bacteria and yeasts. Furthermore, the bioactivity detected was mainly due to the presence of pedopeptins, which are NRPs and whose genes are present in the NL19 genome. These results were supported by RNA-seq and validated by qPCR, which showed that the transcription of pedo_nrps genes was significantly downregulated in cells grown in a high concentration of PC. Also, NL19´ RNA-seq transcriptome data in high and low PC concentrations, allowed us to identify 261 differentially expressed genes (DEGs). In general, at high concentrations of PC, in addition to the genes involved in pedopeptins biosynthesis, genes involved in the de novo biosynthesis of biotin were also found to be significantly downregulated. In this condition genes that encode putative efflux pumps as well as ferrous iron capture system, were significantly upregulated, which suggests redirection of cellular metabolism. Genome mining approaches also revealed that NL19 and its closely related species have an important collection of new NRPS-BGCs. Finally, the pan-genome analyses highlight the genus Pedobacter as a prolific source of relevant new BNPs including NRPs, PKs, RiPPs, hidroxamate, carotenoids and squalene, mainly the NL19 and P. cryoconitis species. The work developed reinforces the relevance of bioprospecting extreme environments. The characterization of the strain P. lusitanus NL19 reveals the enormous, yet still untapped, biotechnological potential of this strain, and also of other members of the genus Pedobacter, for the discovery of new compounds with diverse biotechnological applications, including therapeutic ones.